Dose Optimization of Teicoplanin for Critically Ill Patients With Renal Dysfunction and Continuous Renal Replacement Therapy: Experience From a Prospective Interventional Study - Shi, Lu; Zhuang, Zhiwei; Duan, Lufen; Zhu, Chenqi; Xue, Hongzhi; Wang, Xiao; Xu, Xiaowen; Yuan, Yunlong; Shi, Ling; Li, Jiahui; Sun, Jiantong; Liu, Xin; et al. (Frontiers in Pharmacology, 2022)
Background: Due to the lack of updated information of Teicoplanin (TEI) during continuous renal replacement therapy (CRRT), no exact dosage regimen was recommended. The aim of this study was to optimize the dosage regimen of TEI in renal dysfunction patients with CRRT or not, evaluate the influence factors of the eradication of Gram-positive bacteria, and effect of CRRT on the clearance of TEI. Methods:Patients with renal dysfunction receiving TEI treatment in the ICU were prospectively collected, divided into CRRT group and non-CRRT group. The logistic regression analysis was used to screen the factors affecting the eradication of Gram-positive bacteria. The filtrate concentration of the CRRT group was measured at the time of TEI Cmin, the filtration coefficient of TEI were calculated to evaluate the effect of CRRT on clearance of TEI. Results: A total of 106 patients were included, 40 cases in the CRRT group and 66 cases in the non-CRRT group. After given high-loading doses of TEI, 75.8% and 70% of TEI Cmin in the non-CRRT group and CRRT group were reached the range of 10-30 mg/L before the 3rd dose. There was more risk of G+ uneradicated while the APACHEⅡscore higher than 22.5, the albumin level before the start of TEI administration and before the 6th-8th dose lower than 32.8 g/L and 29.3 g/L, the Cmin before the 3rd dose and 6th-8th dose lower than 13.2 mg/L and 17.1 mg/L, duration of TEI therapy shorter than 10.5 days. The correlation coeffcient (r) was 0.6490 between the Cmin before the 3rd dose and the albumin level (P <0.001).The filtration coefficient of TEI was 10.7 ± 2.4% at Cmin and 11.1 ± 2.5% at Cmax. The GFR had no correlation with filtration coefficient (r = -0.06204; r = -0.08059). The clearance of TEI in CRRT patients was negatively correlated with albumin level (r = -0.6305, P = 0.0013). Conclusion: The early stage of albumin level can significantly affect the initial Cmin and clinical efficacy of TEI, and also had effect on the clearance of TEI by CRRT. The filtration coefficient of TEI was stable, even in a higher ultrafiltration rate.